2019
DOI: 10.1186/s13104-019-4638-9
|View full text |Cite
|
Sign up to set email alerts
|

Scalable methanol-free production of recombinant glucuronoyl esterase in Pichia pastoris

Abstract: Objective Glucuronoyl esterase (GE) is an emerging enzyme that improves fractionation of lignin-carbohydrate complexes. However, the commercial availability of GE is limited, which hinders the research of GE-based bioprocesses for its industrial application in lignocellulose biorefineries. This study evaluated a workable, cost-effective, and commercially scalable production strategy to improve the ease of GE-based research. This strategy consisted of a constitutive and methanol-free enzyme prod… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…From the clones with the methanol-inducible AOX promoter, 69% showed an activity higher than the limit of quantification of the assay, whereas no clone transformed with the GAP-promoter-containing construct produced enzyme activity higher than this limit. While the production of cdh genes under the control of AOX promoter has been well documented [ 33 35 ], there is only limited available data regarding CDH expression under the control of the GAP promoter [ 36 ], despite multiple reports on the use of this expression system for various other lignocellulolytic enzymes [ 37 42 ]. Our analysis shows that the expression system utilizing the AOX promoter was more successful than the GAP promoter to obtain detectable activities of Fs CDH.…”
Section: Resultsmentioning
confidence: 99%
“…From the clones with the methanol-inducible AOX promoter, 69% showed an activity higher than the limit of quantification of the assay, whereas no clone transformed with the GAP-promoter-containing construct produced enzyme activity higher than this limit. While the production of cdh genes under the control of AOX promoter has been well documented [ 33 35 ], there is only limited available data regarding CDH expression under the control of the GAP promoter [ 36 ], despite multiple reports on the use of this expression system for various other lignocellulolytic enzymes [ 37 42 ]. Our analysis shows that the expression system utilizing the AOX promoter was more successful than the GAP promoter to obtain detectable activities of Fs CDH.…”
Section: Resultsmentioning
confidence: 99%
“…The removal of branches of glycuronic acid from hemicellulose can improve the release of fermentable sugars. Conacher et al [108] reported the production and secretion of GE at high yields through constitutive expression in P. pastoris. Li et al [109] expressed Rhizomucor miehei-derived β-mannanase (mRmMan5A), reaching a high level of expression (79,680 U m/L).…”
Section: Pichia Pastorismentioning
confidence: 99%